Automatic fault location for underground low voltage distribution networks. - Navaneethan, S.
This paper describes an automatic fault location technique for permanent faults in underground LV distribution networks (ULVDNs). It uses signals from an existing time domain reflectometry (TDR) instrument. It pre-processes TDR signals to eliminate reflections due to single-phase tee-offs, and to locate 3-phase open or short circuit faults and also uses adaptive filtering to compare the TDR signals to locate faults. In essence, the procedure minimizes the interpretation skill required from a user of a typical TDR based fault location instrument. The relative performance of the system is demonstrated using real field data
Keywords: TDR signals processing; Adaptive filtering; Automatic fault location; Fault location performance; Interpretation skill minimisation; Permanent faults; Three-phase open-circuit faults location; Three-phase short-circuit faults location; Time domain reflectometry instrument; Underground low voltage distribution networks